The 16th international oncolytic virotherapy conference: from in vitro to clinical studies, novel approaches in cancer therapy meeting report - Ekrami, Elena; Ghanbari, Parisa; Othman, Eman M.; Szalay, Aladar A. (Frontiers in Immunology, 2025)
The 16th International Oncolytic Virotherapy Conference, which was held in the vibrant city of Rotterdam, Netherlands, on 27-30th November 2024, featured a variety of novel strategies for improving oncolytic virus therapy. A reflective keynote highlighted industry challenges and lessons. Presentations covered the cutting-edge developments in oncolytic virotherapy from scientific, clinical, and industry perspectives. Young Investigators Talk was a newly introduced segment that debuted this year.